Inference on gravitational waves from coalescences of stellar-mass compact objects and intermediate-mass black holes. Issue 4 (10th February 2016) - Haster, Carl-Johan; Wang, Zhilu; Berry, Christopher P. L.; Stevenson, Simon; Veitch, John; Mandel, Ilya
Abstract : Gravitational waves from coalescences of neutron stars or stellar-mass black holes into intermediate-mass black holes (IMBHs) of ≳100 solar masses represent one of the exciting possible sources for advanced gravitational-wave detectors. These sources can provide definitive evidence for the existence of IMBHs, probe globular-cluster dynamics, and potentially serve as tests of general relativity. We analyse the accuracy with which we can measure the masses and spins of the IMBH and its companion in intermediate-mass-ratio coalescences. We find that we can identify an IMBH with a mass above 100 M⊙ with 95 per cent confidence provided the massive body exceeds 130 M⊙ . For source masses above ∼200 M⊙, the best measured parameter is the frequency of the quasi-normal ringdown. Consequently, the total mass is measured better than the chirp mass for massive binaries, but the total mass is still partly degenerate with spin, which cannot be accurately measured. Low-frequency detector sensitivity is particularly important for massive sources, since sensitivity to the inspiral phase is critical for measuring the mass of the stellar-mass companion. We show that we can accurately infer source parameters for cosmologically redshifted signals by applying appropriate corrections. We investigate the impact of uncertainty in the model gravitational waveforms and conclude that our main results are likely robust to systematics.